2020
DOI: 10.1021/acs.jpcb.0c00769
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Energy of Ions in a Stockmayer Fluid

Abstract: And finally I'd like to acknowledge my parents for raising me the way they did so I could find my way through the world and get to where I am today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Still, further judgment for the model validity is needed to compare with experimental data. Alternatively, the simulation results of the solvation energy of various inorganic monovalent and divalent ions dissolved in nonpolymeric polar solvents are largely consistent with experimental observations 113 . For polymeric solvents, Ganesan and coworkers employed the PSF model to consider ion transport phenomena in polyelectrolytes and found multiple novel properties 114,115 .…”
Section: Electric Polarization and Specific Interaction Of Ilssupporting
confidence: 64%
See 1 more Smart Citation
“…Still, further judgment for the model validity is needed to compare with experimental data. Alternatively, the simulation results of the solvation energy of various inorganic monovalent and divalent ions dissolved in nonpolymeric polar solvents are largely consistent with experimental observations 113 . For polymeric solvents, Ganesan and coworkers employed the PSF model to consider ion transport phenomena in polyelectrolytes and found multiple novel properties 114,115 .…”
Section: Electric Polarization and Specific Interaction Of Ilssupporting
confidence: 64%
“…Alternatively, the simulation results of the solvation energy of various inorganic monovalent and divalent ions dissolved in nonpolymeric polar solvents are largely consistent with experimental observations. 113 For polymeric solvents, Ganesan and coworkers employed the PSF model to consider ion transport phenomena in polyelectrolytes and found multiple novel properties. 114,115 For example, increasing the polymer dielectric constant reduces ionic aggregation at low polymer polarities, whereas polymerÀpolymer and polymerÀion interactions slow polymer segmental motion at higher polymer polarities.…”
Section: Multi-length Scale Effects Of the Electrostatic Interactions...mentioning
confidence: 99%
“…101 In other work with explicit dipoles added to the CG MD model, Shock et al demonstrated that the solvation energy from simulations of Stockmayer fluids (with fixed dipoles embedded within particles) showed good agreement with experimental results, whereas the solvation energy predicted by the Born equation deviates from experiments (Figure 6c). 211 This work suggests that including explicit dipoles can result in better modeling of ion solvation effects.…”
Section: Opportunities and Future Directionsmentioning
confidence: 99%
“…(c) Total solvation energy as a function ionic radius from Stockmayer fluid simulations, experiments, and the Born equation. Adapted with permission from ref .…”
Section: Opportunities and Future Directionsmentioning
confidence: 99%
“…Furthermore, we coarse-grain the cations and anions as spherical beads with each one carrying a positive (+ e ) or negative (− e ) charge at the center in accordance with the Dang force field. 67–72 Given that ion solvation is largely dependent on the ion size, 73,74 we consider a series of ions ( i.e. , Li + , Na + , K + , Cl − , and I − ) with different radii as listed in Table 1.…”
Section: Model and Simulation Detailsmentioning
confidence: 99%